SAT0566 Impact of Disease Management by Rheumatologists and Dermatologists on Patients' Attitude Toward Medication in Psoriatic Arthritis: Results from the Global Align Study. (9th June 2015) - Gladman, D.; Mease, P.; Smolen, J.; Weinman, J.; Kalus, S.; Dorr, A.; Hojnik, M.; Nurwakagari, P.; Selenko-Gebauer, N.
Abstract : Background: Comparative analysis data on disease management and outcomes in patients (pts) with psoriatic arthritis (PsA) treated by dermatologists vs rheumatologists in clinical practice are sparse. Furthermore, data on beliefs about the necessity of treatment in pts with PsA treated by dermatologists vs rheumatologists are lacking. Objectives: The multi-country, cross-sectional ALIGN study determined pts' specific and general beliefs toward medications and their adherence to selected systemic therapies in 6 immune-mediated inflammatory diseases. This subanalysis explored potential differences in beliefs of pts with PsA about the necessity of taking systemic medication (eg, conventional synthetic disease-modifying anti-rheumatic drugs [csDMARD] and tumor necrosis factor inhibitors [TNFi]) when treated by rheumatologists vs dermatologists. Methods: Validated questionnaires, including the Beliefs About Medicines Questionnaire (BMQ; assesses general and specific beliefs toward medications) and Brief Illness Perception Questionnaire (BIPQ; 8 questions to assess illness perceptions), were administered to 7197 eligible pts. Associations were analyzed by multiple linear regression. Results: 635 PsA pts were analyzed (male, 53.7%; mean age, 50.7 y). Most dermatologist-treated PsA pts (68.7%) received TNFi ± steroids, while csDMARDs ± steroids (38.5%) or csDMARD+TNFi combination therapy (35.2%) were mainly given to rheumatologist-treated PsA pts ( P <0.0001; χ 2 test). Significantly shorter mean disease duration, lower prior disease severity, longer maximal treatment duration (all P <0.001), greater perception of the illness to last longer/forever and to have control over the illness (BIPQ items #2, P =0.042; #3, P =0.043), greater "understand the illness feelings" (BIPQ #7, P <0.002; all Wilcoxon test), and higher incidence of skin/subcutaneous tissue disorders ( P =0.011; χ 2 test) were observed in rheumatologist- vs dermatologist-treated PsA pts. Higher scores for the BMQ-Specific Necessity (mean, 19.7 vs 18.6; median, 20 vs 19) and BMQ-Specific Concern (mean, 14.1 vs 13.5; median, 14 vs 13) subscales were seen in rheumatologist-treated vs dermatologist-treated PsA pts. In multiple regression analysis, the mean BMQ-Specific Necessity level of rheumatologist-treated PsA pts was significantly higher than the mean score level of dermatologist-treated PsA pts (adjusted mean difference of 0.88 units; 95% CI: 0.20–1.56; P =0.011). Conclusions: Data from this exploratory analysis suggest that attitudes towards systemic medication differ between pts with PsA treated by rheumatologists and dermatologists. The differences in necessity beliefs between rheumatologist- and dermatologist-treated pts, besides disparities in some clinical characteristics, may be attributed to dissimilar illness perception. Acknowledgements: AbbVie funded the study and the analysis, and approved the abstract for submission. Medical writing assistance was provided by Michael Theisen of Complete Publication Solutions, LLC, and was supported by AbbVie. The authors thank Fabrice Gillas, MD, of AbbVie for his contributions to the ALIGN study. Disclosure of Interest: D. Gladman Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene Corporation, Janssen, Pfizer Inc, Novartis, and UCB, P. Mease Grant/research support from: Celgene Corporation, Novartis, and Roche, Consultant for: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, Janssen, Eli Lilly, Pfizer Inc, and UCB., J. Smolen Grant/research support from: AbbVie Inc., Amgen, AstraZeneca, BMS, Celgene, Centocor-Janssen, Glaxo, Lilly, Pfizer, MSD, Novo Nordisk, Roche, Sandoz, and UCB, Consultant for: AbbVie, Amgen, AstraZeneca, BMS, Celgene, Centocor-Janssen, Glaxo, Lilly, Pfizer, MSD, Novo Nordisk, Roche, Sandoz, and UCB, J. Weinman Employee of: Atlantis Healthcare, S. Kalus Employee of: GKM Gesellschaft fuer Therapieforschung mbH, A. Dorr Shareholder of: AbbVie., Employee of: AbbVie., M. Hojnik Shareholder of: AbbVie., Employee of: AbbVie., P. Nurwakagari Shareholder of: AbbVie., Employee of: AbbVie., N. Selenko-Gebauer Shareholder of: AbbVie., Employee of: AbbVie.